(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
Improving the welfare and benefits of trade union members and employees is an activity of taking care of the material and spiritual life of employees. To provide solutions to improve the welfare of union members and employees of trade unions in the current period, the article will analyze the nature of benefits for union members and employees of trade unions, the current state of welfare and Propose solutions to improve welfare for union members and employees of Vietnam Trade Union in the coming time.